Will you stay or will you go the effects anthropomorphism presence and the marketing mix have on retail app continuance use intention - Lim, Xin Jean; Cheah, Jun Hwa; Ng, Siew Imm; Kamal Basha, Norazlyn; Soutar, Geoff (Elsevier, 2021)
Retail applications (or retail apps) have emerged as a game-changer to complement and enhance the consumer purchase experience. Responding to calls of prior research, this study used the Two-factor Theory to understand how hygiene (i.e., anthropomorphism presence-AP) and motivation factors (i.e., marketing mix- MM) influence consumers’ retail app continuance use intention. Consumer engagement (CE) was investigated as a mediator, while prevention focus and promotion focus were suggested as moderators. Data were collected from 456 Millennial mobile shoppers and analyzed using PLS-SEM. Result from the study's structural model suggested that continuance use intention was dependent on retailers’ effectiveness on engaging with consumers and establishing attractive marketing elements. CE was found to mediate the path between AP and MM on continuance use intention. In addition, Millennial consumers with a high prevention focus was found to emphasize MM components in the engagement process. Some implications and suggestions for further research were discussed.